2009
DOI: 10.3748/wjg.15.3999
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intramuscular diclofenac and fluid replacement in prevention of post-ERCP pancreatitis

Abstract: AIM:To assess the efficacy of intramuscular diclofenac and fluid replacement for prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. METHODS:A prospective, placebo-controlled study was conducted in 80 patients who underwent ERCP. Patients were randomized to receive parenteral diclofenac at a loading dose of 75 mg followed by the infusion of 5-10 mL/kg per hour isotonic saline over 4 h after the procedure, or the infusion of 500 mL isotonic saline as placebo. Patients were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 45 publications
0
57
2
1
Order By: Relevance
“…Nonsteriod antiinflammary drugs (NSAIDs), on the other hand, may be used additionaly for pain management in cases where narcotics have weak effect or alone in cases with mild symptoms. Albeit, the use of NSAIDs have been reported to reduce the frequency of post-ERCP pancreatitis in patients without oddi sphincter dysfunction, due to antiinflammtory effect [54].…”
Section: Pain Managementmentioning
confidence: 99%
“…Nonsteriod antiinflammary drugs (NSAIDs), on the other hand, may be used additionaly for pain management in cases where narcotics have weak effect or alone in cases with mild symptoms. Albeit, the use of NSAIDs have been reported to reduce the frequency of post-ERCP pancreatitis in patients without oddi sphincter dysfunction, due to antiinflammtory effect [54].…”
Section: Pain Managementmentioning
confidence: 99%
“…The rate of stent placement was similar in the NSAID and the placebo groups. Five studies reported that they did not use pancreatic stent for PEP prophylaxis [11,14,[16][17][18].…”
Section: Studies Includedmentioning
confidence: 99%
“…Nine studies, all published as full text articles, were included [10][11][12][13][14][15][16][17][18]. The characteristics and quality of the studies are shown in table 1.…”
Section: Studies Includedmentioning
confidence: 99%
See 2 more Smart Citations